Thematic protonotarioi in Byzantine Empire: about the problem the origin and main functions the institution - Dmitriy Sergeyevich Borovkov (Античная древность и средние века, 2019)
The article is devoted to thematic protonotarioi, the important institution of byzantine thematic administration in IX–XI centuries. The author addresses the problems of determining the time of origin of the post, as well as the reconstruction of its functions primarily on the basis of written sources. The following conclusions: the Institute was originated at the turn of VIII–IX centuries. The main function of these officials was the food supply of civil servants, service, military units of the theme itself, as well as following through its territory. Special responsibility of thematic protonotarioi was to supply the imperial court in a military campaign. The main source of replenishment of food stocks has been a synonae, the natural duties entrusted on population of a theme.